Antioxidant activity of chestnut constituents: flowers, leaves, skins and fruits - Barreira, João C.M. (2011)
In this study, the antioxidant properties of different chestnut constituents (flowers, leaves, skins and fruits) were evaluated through several biochemical assays: DPPH (2,2-diphenyl-1- picrylhydrazyl) radical scavenging activity, reducing power, inhibition of β-carotene bleaching, inhibition of oxidative hemolysis in erythrocytes, induced by 2,2’-azobis(2- amidinopropane)dihydrochloride (AAPH), and inhibition of lipid peroxidation in pig brain tissue through formation of thiobarbituric acid reactive substances (TBARS). These assays have been extensively studied as models for the peroxidative damage in biomembranes. For all the methods EC50 values were calculated in order to evaluate the antioxidant efficiency of each product. The phenol and flavonoid contents were also obtained and correlated to antioxidant activity. Chestnut skins revealed much better antioxidant properties, presenting much lower EC50 values, particularly for lipid peroxidation inhibition in TBARS assay. Also, the highest antioxidant contents (phenols and flavonoids) were found for this constituent.